2016
DOI: 10.1007/s11269-016-1380-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Changes in Spatial Pattern of Drought Using RDI Index in south of Iran

Abstract: Drought is one of the main natural hazards affecting the economy and the environment of large areas. Droughts cause crop losses, urban water supply shortages, social alarm, degradation and desertification. In this study, the spatial characteristics of annual and seasonal drought were evaluated based on climate data from 16 synoptic stations during the period of 1980-2010 in south of Iran. To estimate the drought severity used modified Reconnaissance Drought Index (RDI) and to prepare maps, ArcGis10.2 software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Although several studies have shown that the drought severity in different regions of the world will likely increase with increasing greenhouse gas emissions and global warming over the coming decades and toward the end of the 21 st century 481 (Burke et al, 2006;McGrath et al 2012;Dai, 2013;Trenberth et al, 2014), the regions in the 482 mid-latitudes may be an exception that show a reduction of drought severity by the end of 21 st 483 century (Orlowsky and Seneviratne, 2013;Cook et al, 2014). Our general forecast of increasing 484 droughts around mid-century and recovery in the last decades of the 21st century to levels 485 similar to the present time is thus consistent with previous results and was also predicted by 486 Zarei et al (2016) and Gohari et al (2017) for the Persian Gulf region. Similarly to this study, 487 Zarei et al (2016) and Gohari et al (2017) expect that long-term droughts will occur on southern 488 coast of Iran from the mid-2040s until the mid-2080s, followed by rising rainfall and reduced 489 drought intensity by the end of the 21 st century.…”
supporting
confidence: 88%
“…Although several studies have shown that the drought severity in different regions of the world will likely increase with increasing greenhouse gas emissions and global warming over the coming decades and toward the end of the 21 st century 481 (Burke et al, 2006;McGrath et al 2012;Dai, 2013;Trenberth et al, 2014), the regions in the 482 mid-latitudes may be an exception that show a reduction of drought severity by the end of 21 st 483 century (Orlowsky and Seneviratne, 2013;Cook et al, 2014). Our general forecast of increasing 484 droughts around mid-century and recovery in the last decades of the 21st century to levels 485 similar to the present time is thus consistent with previous results and was also predicted by 486 Zarei et al (2016) and Gohari et al (2017) for the Persian Gulf region. Similarly to this study, 487 Zarei et al (2016) and Gohari et al (2017) expect that long-term droughts will occur on southern 488 coast of Iran from the mid-2040s until the mid-2080s, followed by rising rainfall and reduced 489 drought intensity by the end of the 21 st century.…”
supporting
confidence: 88%
“…Some investigations have warned against ignoring evapotranspiration in drought analysis (Vicente‐Serrano et al ., ; Sun et al ., ; Zhang et al ., ). Some studies have considered ET 0 to characterize the drought conditions in Iran (Zarei et al ., ; Zarei and Moghimi, ). However, the influence of ET 0 inclusion is less studied.…”
Section: Introductionmentioning
confidence: 99%
“…MK trend tests were commonly used to evaluate of trends in series of environmental data, climate data or hydrological data [41]. The MK test statistic S [12] is calculated by using: The standardized normal test statistic Z s is computed as:…”
Section: Mann-kendall (Mk) Trend Testmentioning
confidence: 99%
“…Zarei et al [41] evaluated the spatial pattern of drought in the south of Iran based on Reconnaissance Drought Index (RDI). According to the results of this paper, in a 3-months time scale, the area percentage with dry classes had an increasing trend and areas with the wet condition had a decreasing trend.…”
Section: Introductionmentioning
confidence: 99%